Radiological and nuclear medicine examinations in breastfeeding women. A novel protocol of the Academy of Breastfeeding - Y.L. Gerashchenko (LCC «Medicine-Inform», 2021)
Y.L. Gerashchenko International Medical Center "Sogaz", St. Petersburg, Russian Federation Antenatal Clinic No. 22, St. Petersburg, Russian Federation This paper discusses a particular time in woman's life, breastfeeding, that takes from 4 months to 2 years. Mean age of pregnant women increases every year, while reproductive technologies allow for realizing childbearing function in the second period of adulthood. Many diseases those diagnosis requires multiple examinations occur with age. When the mother is forced to stop breastfeeding in view of the need for examination, it is essential for her to get a reasoned rationale and to know the duration of limitations. Unfortunately, no regulations covering the use of modern nuclear medicine and X-ray technologies in breastfeeding women are available in the Russian Federation. Foreign experience may address the existing lack of knowledge. In the future, these data may provide guidance to develop national recommendations. This review paper summarizes the studies on imaging techniques and nuclear medicine procedures in lactating women and limitations of breastfeeding in their use. Keywords: lactation, breastfeeding, breast examination, nuclear medicine, mammologist. For citation: Gerashchenko Y.L. Radiological and nuclear medicine examinations in breastfeeding women. A novel protocol of the Academy of Breastfeeding. Russian Journal of Woman and Child Health. 2021;4(3):238-242 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-238-242.